1989
DOI: 10.1161/01.hyp.13.6.910
|View full text |Cite
|
Sign up to set email alerts
|

Leucine aminopeptidase M-induced reductions in blood pressure in spontaneously hypertensive rats.

Abstract: Leucine aminopeptidase M significantly reduced blood pressure for up to 40 minutes when infused intracerebroventricularly into anesthetized spontaneously hypertensive rats (SHR) from a mean±SEM of 190±4 to 94±7 mm Hg and also in normotensive Wistar-Kyoto (WKY) rats from 138±5 to 68±8 mm Hg. Cerebrospinal fluid levels of angiotensin II (Ang II) and III were measured by radioimmunoassay and indicated drops with leucine aminopeptidase M infusion in SHR (from 36±6 to 11±1 pg/100 fil) and in WKY rats (from 33±9 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In this review, we will describe the enzymatic properties of the M1 family of aminopeptidases, which mediate the metabolism of BP regulatory peptides and may thus function as regulators of BP in physiological and/or pathological conditions. hypertensive rats (SHR) by Wright et al [4][5][6]. While the injection of APA significantly increased BP, that of APN(M) caused a decrease of BP.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we will describe the enzymatic properties of the M1 family of aminopeptidases, which mediate the metabolism of BP regulatory peptides and may thus function as regulators of BP in physiological and/or pathological conditions. hypertensive rats (SHR) by Wright et al [4][5][6]. While the injection of APA significantly increased BP, that of APN(M) caused a decrease of BP.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these data, Wright et al [16] showed that, despite the high molecular mass of APA and APN (∼ 120-130 kDa for the monomer), the ICV infusion of APA results in a significant increase in BP, whereas the ICV injection of APN into SHR decreases BP [52]. The hypertensive effect probably results from higher levels of brain Ang III production, whereas the hypotensive effect may be related to an increase in Ang III metabolism.…”
Section: Angiotensin III and Central Control Of Blood Pressurementioning
confidence: 84%
“…infusion of APA results in a significant increase in BP [68] whereas the i.c.v. injection of APN into SHR decreases BP [65]. The hypertensive effect probably results from higher levels of brain AngIII production, whereas the hypotensive effect may be related to an increase in AngIII metabolism.…”
Section: Identification Of the In Vivo Metabolic Pathways Of Angii Anmentioning
confidence: 93%
“…AngII and AngIII injected separately i.c.v. into normotensive Wistar Kyoto (WKY) rats or SHR, cause similar dose-dependent pressor responses [52,64,65]. In addition, AngIII, applied by microiontophoresis, induces an increase in firing rate of neurons higher than AngII in two brain structures involved in the control of BP, the SFO [66], and Heart Fail Rev (2008) 13:311-319 313 the PVN [53].…”
Section: Identification Of the In Vivo Metabolic Pathways Of Angii Anmentioning
confidence: 99%